1989
DOI: 10.1159/000125279
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution of Immunoreactive Somatostatin in the Bovine Pineal Gland

Abstract: Regional distribution of immunoreactive somatostatin (IRS) and melatonin were investigated in the bovine pineal gland. The total IRS and melatonin content ranged from 0.26 to 2.28 pmol, and from 19.4 to 42.7 pmol, respectively, per bovine pineal. Reverse phase liquid chromatography of pineal extracts demonstrated that more than 90% of IRS coeluted with synthetic somatostatin-14 and somatostatin-28. While the IRS content was shown to vary considerably throughout the gland, with a constant and marked maximal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
9
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…9). The presence of both somatostatin-14 and somatostatin-28 is in accord with previous HPLC analysis of bo vine extract [9] in which analysis it was shown that 90% of the somatostatin immunoreactive extract coeluted with these two somatostatin molecules. The positive staining with antiserum No.…”
Section: P R O S O M a T O S T A T I Nsupporting
confidence: 91%
See 2 more Smart Citations
“…9). The presence of both somatostatin-14 and somatostatin-28 is in accord with previous HPLC analysis of bo vine extract [9] in which analysis it was shown that 90% of the somatostatin immunoreactive extract coeluted with these two somatostatin molecules. The positive staining with antiserum No.…”
Section: P R O S O M a T O S T A T I Nsupporting
confidence: 91%
“…This finding is also in accord with an analysis of bovine somatostatin immunoreactive material from the same re gions [9] in which study the rostral part of the gland was shown to contain a higher concentration of somatostatinimmunoreactive material than the distal part of the gland. These findings, together with the observation that fibers from the pineal stalk are connected with intrapineal nerve fibers, strongly indicate a somatostatinergic central in nervation of the pineal in the bovine.…”
Section: P R O S O M a T O S T A T I Nsupporting
confidence: 88%
See 1 more Smart Citation
“…The presence of SOM in the pineal gland was shown for the first time by Pelletier et al (1975) in the rat (and later on by Pévet et al, 1980b;Finley et al, 1981;Webb et al, 1984;Møller et al, 1995) then in the hamster, gerbil, mouse (Webb et al, 1984), sheep, pig (Lew and Lawson-Willey, 1987), cow (Peinado et al, 1989;Møller et al, 1992), and human (Bouras et al, 1987). The rat pineal gland contains approximately 0.3 to 3 ng SOM/mg protein (Webb et al, 1985).…”
mentioning
confidence: 99%
“…The SOMergic fibers are not of sympathetic origin since the pineal content of SOM is not modified after SCGx (Webb et al, 1984(Webb et al, , 1985. It is proposed that these fibers could be of central origin because the number of SOMergic fibers and the peptide concentration are 4 times higher in the MULTIPLE REGULATION OF PINEAL MELATONIN SYNTHESIS IN MAMMALS proximal than in the distal area of the gland (Peinado et al, 1989;Møller et al, 1992).…”
mentioning
confidence: 99%